Analysis of hot air heat extractor for vehicle cabin - Sasheendran, Kuppusamy (2008)
A vehicle parked under direct sunlight for a few hours will have a hot cabin. Besides creating an uncomfortable situation, this actually affects the lifetime of the vehicle’s interior and accessories such as seats, carpets and door panels. We experience it all the time when we park under the hot sun or in a non-cooled garage. After only a short time our car becomes a virtual oven. We open the door and the oppressive heat hits us. Everything we touch burns like a hot plate. Our dashboard vinyl eventually begins to crack and our leather interior becomes dry and brittle. The health risk involved when entering a sweltering car can damage our lungs and become life threatening. This happens because air flow from interior to exterior takes place in a very small volume and velocity. The simulation started by taking temperature, flow velocity, type of flow, cabin volume and time into consideration. A Proton Iswara Hatchback’s cabin used as the air flow boundary. The simulation shows difference in air flow and temperature out of the cabin when a couple of DC fans installed to the spots where the most heat is generated. The expected result is that the increase in air flow from cabin to out of the car would decrease the temperature in the cabin. In this project, the main idea is to increase the air flow out of the car as much as possible to ensure the cabin temperature is kept to the level intended. As the conclusion, the added fans give impact to the cabin temperature of car.